Body sway responses to pseudorandom support surface translations of vestibular loss subjects resemble those of vestibular able subjects - Lippi, V.; Assländer, L.; Akcay, E.; Mergner, T. (Neuroscience letters, 2020)
•We compared responses to support surface translations of vestibular-able and vestibular-loss subjects.•Eyes-closed and eyes-open conditions were tested· The support surface was translated in anterior-posterior direction. Motion profiles were constructed from pseudo-random-ternary sequences (PRTS).•Vestibular-able closely resembled those of the vestibular-loss subjects for both Eyes-closed and eyes-open.•Visual conditions had a strong effect on the response producing two specific response patterns. Body sway responses evoked by a horizontal acceleration of a level and firm support surface are particular in that the vestibular information on body-space angle BS resembles the proprioceptive information on body-foot angle BF. We compared corresponding eyes-closed responses of vestibular-able (VA) and vestibular-loss (VL) subjects, postulating a close correspondence. In contradistinction to previous studies, we used an unpredictable (pseudorandom) stimulus and found that the eyes-closed and eyes-open responses of the VA closely resembled those of the VL subjects, as expected. We further conclude that the vestibular signals coding head linear translation in VA subjects has in this case too little functional relevance to cause a notable difference between the subject groups.